2017
DOI: 10.3390/sym9030040
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Sexually-Dimorphic Asymmetric Development of the Ferret Cerebellar Cortex

Abstract: Abstract:A three-dimensional (3D) T 1 -weighted Magnetic Resonance Imaging (MRI) at 7-Tesla system was acquired with a high spatial resolution from fixed brains of male and female ferrets at postnatal days (PDs) 4 to 90, and their age-related sexual difference and laterality were evaluated by MRI-based ex vivo volumetry. The volume of both left and right sides of cerebellar cortex was larger in males than in females on PD 10 and thereafter. When the cerebellar cortex was divided into four transverse domains, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Although the processes of cortical histogenesis and sublobulation of the vermis in rats were simultaneously accomplished by PD 21 (Altman & Bayer, 1997), the vermis was further sublobulated in ferrets after the completion of the formation of cortical histocytoarchitectures at PD 42. In our previous study, we observed that sexual dimorphism of the ferret cerebellum was distinct on PD 42 on the basis of the appearance of the counterclockwise torque asymmetry in males but not in females (Sawada & Aoki, 2017). Further study will be needed to examine the process of sublobulation of the vermis in male and female ferrets in relation to the sexual dimorphic asymmetric development of the cerebellum.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the processes of cortical histogenesis and sublobulation of the vermis in rats were simultaneously accomplished by PD 21 (Altman & Bayer, 1997), the vermis was further sublobulated in ferrets after the completion of the formation of cortical histocytoarchitectures at PD 42. In our previous study, we observed that sexual dimorphism of the ferret cerebellum was distinct on PD 42 on the basis of the appearance of the counterclockwise torque asymmetry in males but not in females (Sawada & Aoki, 2017). Further study will be needed to examine the process of sublobulation of the vermis in male and female ferrets in relation to the sexual dimorphic asymmetric development of the cerebellum.…”
Section: Discussionmentioning
confidence: 97%
“…Male ferrets consisting of four animals each at five different postnatal days (PDs), that is, 4, 10, 21, 42, and 90, were purchased from SLC (Hamamatsu, Japan). The postnatal ages were identical to those examined in our previous study (Sawada & Aoki, 2017) for comparison with magnetic resonance imaging‐defined volumetric findings in the developing cerebella of ferrets. The pups were reared with lactating mothers (two or three pups/mother) and housed in stainless‐steel cages (80 cm × 50 cm × 35 cm) at 21.5 ± 2.5°C under artificial lighting for 12 hr at the Faculty of Animal Breeding, Nakaizu Laboratory, SLC.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, morphological and functional lateralization was observed in other brain regions. Several studies have reported on the cerebellar asymmetry in mammalian species such as humans [47], chimpanzees [38], capuchins [38], ferrets [60][61][62], and dogs [63]. Cerebellar asymmetry is known to involve the large-scale fiber connections, which have a contralateral linkage to the cerebellar hemispheres with the cerebral association cortices [64].…”
Section: Discussionmentioning
confidence: 99%